Receptor for advanced glycation end products is overexpressed in psoriatic plaques independent of disease severity - Karaismailoglu, Eda; Aktas, Akin; Sungu, Nuran; Ozgor, Ozkay; Akoglu, Gulsen (Scientific Scholar, 2017)
Enhanced expression and excitation of the receptor for advanced glycation end products is considered to play a role in the regulation of many pro-inflammatory genes involved in the pathogenesis of psoriasis.We investigated the expression of receptor for advanced glycation end product in various cell types, in lesional and peri-lesional skin of patients with psoriasis, and its correlation with disease severity.Paraffin-embedded punch biopsy tissue taken from psoriatic plaques and peri-lesional normal appearing skin tissue of twenty patients with psoriasis, and normal skin samples of eleven healthy participants, were enrolled in the study. The sections were stained immunohistochemically with anti-receptor for advanced glycation end product antibody. The intensity of receptor for advanced glycation end product expression was assessed semi-quantitatively on epidermal cells, microvascular endothelium, dermal fibroblasts and inflammatory cells. They were graded as follows: 0 (no staining), 1 (weak), 2 (moderate) and 3 (strong) intensity.Receptor for advanced glycation end product expression on epidermis, microvascular endothelium, inflammatory cells and fibroblasts in the psoriatic plaques was more intense than perilesional and normal tissue (all P < 0.05). It did not correlate with disease severity.The main limitation of our study is that this was a semi-quantitative assessment, detected immunohistochemically in skin biopsies.Receptor for advanced glycation end product expression may have an important role in psoriasis pathogenesis, independent of disease severity.
Keywords: Adult; Male; Receptor for Advanced Glycation End Products; Gene Expression; Middle Aged; Severity of Illness Index; Humans; Psoriasis; Female; Prospective Studies; 3. Good health